Reflecting on being an effective teacher in an age of measurement. Issue 2 (4th March 2018) - Goodley, Claire
Abstract: This reflective study examines what effective means in terms of teaching in secondary schools in England. The article questions whether quality assurance and observations produce better teachers or better 'fabricators'. The study explores the pressures of performativity and the resulting fabrication: the 'ticking of boxes' in order to be classed as 'outstanding' and 'effective'. A journey to recapture the pleasure in teaching and learning through reflective diaries will be considered. Here the process leads to the outcome without an overemphasis on assessment criteria and performativity or extrinsic motivators which can counter intrinsic motivation and professional judgement.